CURRÍCULO INTEGRADO DO PROEJA: concepção e implementação no IFMA. - CASTRO, Eunice (2017)
The present dissertation integrates the research line Educational Institutions, Curriculum, Training and Teaching of the Post-Graduation Program in Education of the Federal University of Maranhão. Its general objective is to investigate the integrated curriculum advocated by PROEJA, analyzing its constitution at the level of the official discourse and its implementation within the framework of the Federal Institute of Science and Technology Education of Maranhão -IFMA. We adopted as theoretical guidance the studies of Goodson (2013), Lopes; Macedo (2011) Moreira (2012), Sacristán (2013), Silva (2015), Vasconcelos (2011) for understanding the curriculum conception, on the integrated curriculum Ciavatta (2015), Frigoto (2012), Kuenzer (1998), Ramos (2011, 2012); with respect to EJA Fr eire (1987), Arroyo (2006), Di Pierro; Haddad (2000, 2007), and to PROEJA Moura (2006), Maron (2016), among others. , in addition to the Basic Document of PROEJA, the Curricular Guidelines for Professional Education, Laws and Decrees, as well as institutional documents. We used as a theoretical-methodological approach the qualitative research, by the proximity of an investigation that highlights the meaning that is the product of an interpretative process Lessard-Hérbeth (1990) and Poupart (2010), driven by a method that adopts as categorization the multiple determinations and contradictions in a constant movement, in order to know the reality in a social totality Kosík (1976) and Gamboa (2012), being therefore relevant to understand the phenomenon in its social totality: advances, mishaps and obstacles of the integrated curriculum of the Course technician in Administration of PROEJA of the IFMA, Santa Inês. The data obtained in the research led to the conclusion that the program is seen as a possibility of inclusion, since it seeks to guarantee the reestablishment of the right to education, with the insertion in an Institution that aims at the integrated formation, providing the professionalization and preparation for the world of work. We perceive in the vi ew of managers, teachers and students that the program gains this attribute of inclusion, because it favors the insertion in other spaces, since it is a Program geared towards a broad formation. The research revealed the need to reformulate the Plan of the Technical Course in Administration of the Santa Inês campus, considering aspects inherent to the very nature of the EJA. It also revealed that, in the view of the managers and teachers, the resumption of schooling by the students is difficult, considering the time of absence from school, working time, difficulties of understanding caused by delays in schooling, but also stated that they return with much willpower to study. It made it possible to explain that in the context of youth and adult education, and specifically in professional education, the training of teachers is a challenging issue, as there is still inadequate training for IFMA teachers in a broad context, and specifically in the Santa Inês campus. The essential question is to understand the conceptions of this integrated curriculum and the bases that support it as a way to make possible the organization of the pedagogical work of the school.